Climate Change and Environmental Influence on Prevalence of Visceral Leishmaniasis in West Pokot County, Kenya - Bulle Abdullahi; Joshua Mutiso; Fredrick Maloba; John Macharia; Mark Riongoita; Michael Gicheru (Journal of Tropical Medicine, 2022)
Kala-azar is a parasitic disease caused by Leishmania species transmitted by sand fly. In Kenya, kala-azar is endemic in thirty subcounties spread over in eleven counties in the arid zones. Climate change-influenced seasonal weather variability and environmental alterations remain important determinants of many vector-borne diseases. The present study focused on climate change and environmental influence on kala-azar in West Pokot. A descriptive cross-sectional and retrospective research design was adapted. Study area was purposively selected. Locations were randomly selected, and households were systematically selected. Three hundred sixty-three household questionnaires, eleven key informant interviews, and five focus group discussions were undertaken. Secondary data were obtained from Kacheliba subcounty hospital records. Statistical Package for the Social Sciences version 24 was used to analyze quantitative data while qualitative data were analyzed to establish connection for interpretation. Kala-azar cases have been on the rise on aggregate and surge towards the end of dry season and just after the rains. Significant environmental factors included the presence of seasonal rain water pathways and rock piles around houses (AOR = 4.7; 95% CI = (2.3-9.6), p<0.05), presence of acacia trees in and around homesteads (AOR = 8.5; 95% CI = (2.5-28.6), p<0.05), presence of anthills around the homesteads (AOR = 5.2; 95% CI = (1.2-23.4), p<0.05), and presence of animal shed within compound (AOR = 2.8; 95% CI = (0.96-8), p<0.05). Climate change-induced seasonal weather variability, increased temperature and reduced precipitation as well as environmental alterations influence kala-azar occurrence in West Pokot. Community sensitization on disease prevalence, clearing of vector predilection sites, and improving community environmental risk perception are imperative to promote prevention.